Inactivating histone deacetylase HDA promotes longevity by mobilizing trehalose metabolism - Ruofan Yu (Nature Portfolio, 2021)
Histone acetylations are important epigenetic marks for transcriptional activation and respond to metabolic changes. Here the authors develop a lifespan screen and show that inactivation of the histone deacetylase complex activates longevity and protects against stress via trehalose metabolism.